1997
DOI: 10.1179/joc.1997.9.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antimicrobial Agents on the Piliation ofPseudomonas aeruginosaand Adherence to Mouse Tracheal Epithelium

Abstract: The effect of subminimal inhibitory concentrations (sub-MICs) of antimicrobial agents on the adherence of Pseudomonas aeruginosa (pili+) to trachea mucosal cells, the first stage in the development of P. aeruginosa respiratory tract infections, was investigated. The adherence of P. aeruginosa to the cells of the lower respiratory tract using a model of acid-injured trachea in mice was observed by electron microscopy (transmission and scanning). When P. aeruginosa was cultured with 1/4 MIC of erythromycin, mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…A number of antibiotics have been shown to impair bacterial adherence. 50 Yamasaki and collaborators 51 have provided evidence that exposure of P. aeruginosa to erythromycin at 1/4 MIC for only 4 h signifi cantly reduced the number of pili and, hence, adherence. Another important cell-surface structure is the fl agellum, which provides bacterial motility and adherence, and enables the bacteria to establish a colony in a more hospitable environment.…”
Section: Bacterial Cell-surface Structures and Adherence To Host Cellsmentioning
confidence: 97%
“…A number of antibiotics have been shown to impair bacterial adherence. 50 Yamasaki and collaborators 51 have provided evidence that exposure of P. aeruginosa to erythromycin at 1/4 MIC for only 4 h signifi cantly reduced the number of pili and, hence, adherence. Another important cell-surface structure is the fl agellum, which provides bacterial motility and adherence, and enables the bacteria to establish a colony in a more hospitable environment.…”
Section: Bacterial Cell-surface Structures and Adherence To Host Cellsmentioning
confidence: 97%
“…These include bacterial synthesis of the cell wall and extracellular products, bacterial adherence to cells, and changes in bacterial morphology [21,22]. SubMIC EM reduces PA adherence to acid-injured murine tracheal mucosa [23], PA ciliotoxin, haemagglutinin and protease production [24,25], neutrophil migration [26], and superoxide generation [26]. SubMIC macrolides suppress biofilm formation by PA, which also appears to be an important factor for PA to persist in the lungs of patients with bronchiectasis and CF [27].…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose erythromycin also altered P. aeruginosa morphology and reduced adherence to human type IV basement membrane collagen in vitro (305). Yamasaki et al (332) showed that exposure of P. aeruginosa to a sub-MIC level of erythromycin reduced the number of pili and, hence, adherence. Erythromycin suppresses the production of P. aeruginosa hemagglutinins, including the adhesins lectins as well as extracellular protease, hemolysin, and homoserine lactone autoinducers (266).…”
Section: Inhibition Of Adherencementioning
confidence: 99%